Attention deficit hyperactivity disorder: concomitant diseases with an emphasis on epilepsy - O. A. Pylaeva; A. A. Shatenshtein; K. Yu. Mukhin (Русский журнал детской неврологии)
Attention deficit hyperactivity disorder (ADHD) is the most common cause of behavioral disorders and learning difficulties in preschool and school-age children. Patients with ADHD are often diagnosed with concomitant diseases, which creates additional diagnostic and therapeutic challenges and leads to a more significant reduction in the quality of life. ADHD is often associated with epilepsy: ADHD manifestations are more common in individuals with epilepsy, and vice versa, patients with ADHD are more likely to have epilepsy. The estimated prevalence of ADHD in children is 7–9 %, whereas in children with epilepsy, it reaches 20–50 %. Epilepsy is also one of the most common diseases in children (affecting approximately 1 % of the pediatric population), which is often aggravated by concomitant diseases, including cognitive, behavioral and emotional disorders. Various factors, such as characteristics of epileptic process and lesions in particular portions of the brain, can underlie the development of ADHD in epilepsy. Epileptiform activity and adverse effects of antiepileptic drugs can also play an important etiological role. Some antiepileptic drugs (such as barbiturates) may cause symptoms similar to those in ADHD (in this case, inattentiveness and hyperactivity shall be considered as adverse events that can be reduced or eliminated after cessation of the drug) or exacerbate ADHD symptoms in patients with these disorders. Therefore, the drugs with no negative impact on concomitant diseases or with a positive therapeutic effect for both diseases are preferable in these cases.High prevalence of the ADHD/epilepsy combination leads to a greater reduction in the quality of life, suggesting high relevance of this problem and requiring a revision of therapeutic approaches.